Establishing a peritoneal dialysis technique survival core outcome measure: A standardised outcomes in nephrology-peritoneal dialysis consensus workshop report - Elphick, Emma H; Manera, Karine E; Viecelli, Andrea K; Craig, Jonathan C; Cho, Yeoungjee; Ju, Angela; Shen, Jenny I; Wilkie, Martin; Anumudu, Samaya; Boudville, Neil; Chow, Josephine SF; Davies, Simon J; et al. (SAGE Publications, 2024)
Background: Technique survival, also reported with negative connotations as technique failure or transfer from peritoneal dialysis to haemodialysis, has been identified by patients, caregivers and health professionals as a critically important outcome to be reported in all trials. However, there is wide variation in how peritoneal dialysis technique survival is defined, measured and reported, leading to difficulty in comparing or consolidating results. Methods: We conducted an online international consensus workshop to establish a core outcome measure of technique survival. Discussions were analysed thematically. Results: Fifty-five participants including 14 patients and caregivers from 13 countries took part in facilitated breakout discussions using video-conferencing. The following themes were identified: capturing important aspects of the outcome (requiring a core event to define the outcome, distinguishing temporary from permanent events, recognising heterogeneous experiences of transfers), adopting appropriate neutral nomenclature (conveying with clarity, avoiding negative connotations), and ensuring feasibility and applicability (capturing data relevant to clinical and research settings, ease of adoption). The suggested definitions for the core outcome measure were ‘the event of a transfer to haemodialysis’, or ‘discontinuation of peritoneal dialysis’. Applying the principles described within the workshop, defining the outcome measure as a ‘transfer to haemodialysis’ was preferable. Conclusions: It is proposed that the core outcome of technique survival is redefined as ‘transfer to haemodialysis’ and that its components are standardised using simple, neutral terminology Components considered important by stakeholders included recording the reasons for transfer from peritoneal dialysis, and focussing on permanent events whilst ensuring the outcome remains easy to implement.
Keywords: outcome measures; Technique survival; transfer to haemodialysis